PROFESIONALISME GURU PAI SEBAGAI PILAR PENDIDIKAN KARAKTER DI ERA GLOBALISASI - Mahfudah, Sahila Nur; Munawir, Munawir; Fitriyah, Zakiyatul (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
This study examines the professionalism of Islamic Education (PAI)teachers as a pillar of character education in the era of globalization.The research employs a qualitative descriptive approach with aliterature review method, analyzing various sources, including journalarticles, books, and official documents. The findings highlight that PAIteachers play a crucial role in shaping studentsâ€™ character throughmoral education, role modeling, and guidance. However, challengessuch as the rapid advancement of technology, cultural shifts, and thelack of teacher training hinder the effective implementation of charactereducation. To address these challenges, teachers must integrateinnovative teaching strategies, utilize digital learning tools, andcollaborate with parents and the community. This study underscoresthe necessity for continuous teacher development to ensure thatcharacter education remains relevant and effective in the face ofglobalization.Â